Green supply chain management, economic growth and environment: A GMM based evidence. (1st June 2018) - Rehman Khan, Syed Abdul; Zhang, Yu; Anees, Muhammad; Golpîra, Hêriş; Lahmar, Arij; Qianli, Dong
Abstract: The aim of this research is to examine the relationship between green logistics operations and energy demand, economic growth and environmental sustainability need to make factors for relationship clearer in a panel data of 43 different countries around the globe. The study employed panel Generalized Method of Moments (GMM) estimates for robust inferences. The results have revealed that logistics operations consume energy and fossil fuel, while the amount of fossil fuel and non-green energy sources create significant harmful effect on the environmental sustainability and also have negative effect on economic growth. In addition, poor transport-related infrastructure and logistics service are a major contributor of CO2 and total greenhouse gas emissions. However, carbon emission damages fauna and flora, and reduces economic growth. The findings suggest that renewable energy sources and green practices can mitigate harmful effect of logistics operations on environmental sustainability and spur economic activities with greatly export opportunities in a region.